SHOX2 and WT1 Promoter Methylation Correlates with the Lung Cancer in Iranian Patients - Mohammad taghi khatibi; shahla Mohammad Ganji; Somayeh Chavoshei; Arda Kiani; Seyed Mostafa Hosseini; Mahmoud Tavallaie (Journal of Sciences, Islamic Republic of Iran)
Lung cancer is among the most common cause of cancer death in the world. Since the disease is diagnosed in the middle or late stages of the cancer development a more efficient method for an early diagnosis of the disease is required. The main goal of this study was to investigate the correlation between aberrant promoter methylation of the two genes: SHOX2(Short stature homeobox 2) and WT1(Wilms’ tumor gene1), in the plasma samples of the Iranian lung cancer patients. Following filling questionnaires and obtaining the consent of all participants, 70 cases including 45 patients and 25 healthy controls who underwent bronchoscopy procedure in the Masih-Daneshvari Hospital in Tehran, the blood samples were collected. DNA extraction was done and treatment was performed by sodium bisulfite applying Qiagen DNA methylation kit and Methylation specific PCR(MSP) was performed. The results showed a frequency of 82.2% and 55.55% of the hypermethylation for the SHOX2 and WT1 gene promoters in the caces samples, respectively. Our study demonstrated that hypermethylation of SHOX2 and WT1 genes promoter regions might be involved in lung cancer. The methylation of SHOX2 and WT1 in the blood plasma could be considered as the competent biomarkers for an early diagnosis of the lung cancer as a noninvasive method.